IMAM MALIK'S PROMINENCE IN THE FIELD OF HADITH: A PROFESSIONAL PERSPECTIVE - Zainal Badri, Khairul Nizam Bin (Risâlah, Jurnal Pendidikan dan Studi Islam, 2022)
This paper aims to explore about Imam Malik’s prominence in the field of hadist as a profesional perspective. Professionalism is the ability, skills and methods of implementation that justify a person has expertise in a field. A person is considered a professional when there are values ​​and beliefs of society towards him. This paper seeks to examine the professionalism of Imam Malik bin Anas in the field of hadith. The method used is qualitative while the library approach is the core in collecting and organizing information. The objective of this study is to highlight the prominence of Imam Malik in the field of hadith, especially from the aspect of education, analyze the professionalism of Imam Malik and its significance to the field of psychology, and see the contribution of Imam Malik in terms of professionalism-intellectual relationship, especially in terms of knowledge culture. Also discussed is the influence of Imam Malik's work entitled Al-Muwatta 'on Muslims, especially in terms of the development of knowledge.